(In)Habitings: A Poiesis of Presence/Absence in Love and Longing - Vinz, Ruth (Art/Research International)

(untitled) (University of Alberta, 2022)
“(In)habitings” explores how the death of my father in a Japanese prison in 1945 during World War II and the recent death of my mother entangle in ways that challenge a binary conception of presence and absence as physical proximity or locatedness based on temporal/spatial constructs. The intention of this poetic inquiry is to compose (in)habitings: performative texts of poiesis, in which the data—material (memorabilia, photographs, objects, letters), embodied (sensorium, affects, (re)memberings, animate and inanimate) and multi-contextual (across temporal, spatial, subjective, and social)—are gathered to reorient time, space, and proximities to trace the intensities, contours, and resonances of presence and absence as they modulate to affect love and longing. Conceiving poetic inquiry as a space for exploring, perceiving, and imagining, I present the poetic (art-making rendered in lyrical-figural languages) and simultaneously the inquiry (the research-method) through poems, lyrical narratives, and metaphoric, speculative reveries that converge to explore the poetic, ephemeral, and shimmering data of life/lived worlds where longing—a kind of ache in both method and subject—resides in the spaces of in-between-ness.